2018
DOI: 10.7554/elife.41426
|View full text |Cite
|
Sign up to set email alerts
|

Translesion polymerase kappa-dependent DNA synthesis underlies replication fork recovery

Abstract: DNA replication stress is often defined by the slowing or stalling of replication fork progression leading to local or global DNA synthesis inhibition. Failure to resolve replication stress in a timely manner contribute toward cell cycle defects, genome instability and human disease; however, the mechanism for fork recovery remains poorly defined. Here, we show that the translesion DNA polymerase (Pol) kappa, a DinB orthologue, has a unique role in both protecting and restarting stalled replication forks under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 65 publications
6
81
0
Order By: Relevance
“…3E, 3F). Consistent with previous reports (Coquel et al, 2018;Tonzi & Yin, 2018), depletion of SMARCAL1 slightly increased IdU/CldU ratio in control knockdown cells ( Fig. 3E), though the underlying reason is unclear.…”
Section: Nascent Strand Degradation Caused By Cst Deficiency Requiressupporting
confidence: 92%
“…3E, 3F). Consistent with previous reports (Coquel et al, 2018;Tonzi & Yin, 2018), depletion of SMARCAL1 slightly increased IdU/CldU ratio in control knockdown cells ( Fig. 3E), though the underlying reason is unclear.…”
Section: Nascent Strand Degradation Caused By Cst Deficiency Requiressupporting
confidence: 92%
“…We noticed that loss of TLS polymerase PolÎș partially phenocopies the fork stability defect in KR cells, suggesting that PolÎș is one of the DNA polymerases involved in PCNA ubiquitination-mediated gap filing. However, DNA2 inhibition did not completely rescue the fork protection defect of PolÎș-depleted cells, and indeed it was previously shown that loss of this polymerase results in MRE11-mediated fork degradation (Tonzi et al, 2018). This indicates that PolÎș also plays a role in fork protection independently of PCNA ubiquitination.…”
Section: Pcna Ubiquitination and The Regulation Of Lagging Strand Repmentioning
confidence: 85%
“…Nbs1-dependent phosphorylation of RPA2 recruits the MRN complex to DNA and involves extensive end-resection. A recent study found that hpol k protects stalled forks from Mre11 exonuclease activity to promote fork recovery (76). It is possible TDO inhibition in glioma cells leads to down-regulation of hpol k, which then results in both (a) diminished Chk1 activation and (b) increased resection by the MRN complex.…”
Section: Discussionmentioning
confidence: 99%